SMER28 is a mTOR-independent small molecule enhancer of autophagy that protects mouse bone marrow and liver against radiotherapy - Koukourakis, M; Giatromanolaki, A; Fylaktakidou, K; Sivridis, E; Zois, C; Kalamida, D; Mitrakas, A; Pouliliou, S; Karagounis, I; Simopoulos, K; Ferguson, D; Harris, A (Springer, 2018)
Effective cytoprotectors that are selective for normal tissues could decrease radiotherapy and chemotherapy sequelae and facilitate the safe administration of higher radiation doses. This could improve the cure rates of radiotherapy for cancer patients. Autophagy is a cytoplasmic cellular process that is necessary for the clearance of damaged or aged proteins and organelles. It is a strong determinant of post-irradiation cell fate. In this study, we investigated the effect of the mTOR-independent small molecule enhancer of autophagy (SMER28) on mouse liver autophagy and post-irradiation recovery of mouse bone marrow and liver. SMER28 enhanced the autophagy flux and improved the survival of normal hepatocytes. This effect was specific for normal cells because SMER28 had no protective effect on hepatoma or other cancer cell line survival in vitro. In vivo subcutaneous administration of SMER28 protected mouse liver and bone marrow against radiation damage and facilitated survival of mice after lethal whole body or abdominal irradiation. These findings open a new field of research on autophagy-targeting radioprotectors with clinical applications in oncology, occupational, and space medicine.